Building Sustainable Pesantren Financial Accountability: Family Culture Transformation in Governance System - Ammar Tsaqif; Masiyah Kholmi; Driana Leniwati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Good Corporate Governance (GCG) is an essential principle in ensuring accountability in Islamic educational institutions, including pesantren. This study investigates the role of family culture in enhancing financial accountability within pesantren's governance systems. The research problem arises from the lack of formal financial management systems in many pesantren, leading to reduced public trust and sustainability. The research aims to explore how family-based leadership can support the development of transparent and accountable financial management practices in pesantren. A qualitative case study approach was employed at Pondok Pesantren Nurul Ulum in Malang, East Java, involving interviews with key management members. Findings indicate that while the pesantren lacks formal regulations regarding public funding sources and sanctions, its family-based leadership fosters accountability through strong internal control and moral responsibility. The study concludes that incorporating family values into financial governance can enhance transparency and sustainability in pesantren management.